Development of device for self-sustained gas discharge using high voltage generator; Перспективы развития фундаментальных наук; Т. 1 : Физика - Krotkevich D. Dmitry; Akimchenko I. O.; Buyluk A. O.; Zelentsov D. M.; Demyanenko N. V. Natalia Vladimirovna (2016, 2016)
Заглавие с титульного экрана